Advanced Nanostructured Conjugated Microporous Polymer Application in a Tandem Photoelectrochemical Cell for Hydrogen Evolution Reaction. Issue 37 (15th August 2022) - Barawi, Mariam; Alfonso‐González, Elena; López‐Calixto, Carmen G.; García, Alberto; García‐Sánchez, Alba; Villar‐García, Ignacio J.; Liras, Marta; de la Peña O'Shea, Victor A.
Abstract: Solar energy conversion through photoelectrochemical cells by organic semiconductors is a hot topic that continues to grow due to the promising optoelectronic properties of this class of materials. In this sense, conjugated polymers have raised the interest of researchers due to their interesting light‐harvesting properties. Besides, their extended π‐conjugation provides them with an excellent charge conduction along the whole structure. In particular, conjugated porous polymers (CPPs) exhibit an inherent porosity and three‐dimensional structure, offering greater surface area, and higher photochemical and mechanical stability than their linear relatives (conjugated polymers, CPs). However, CPP synthesis generally provides large particle powders unsuitable for thin film preparation, limiting its application in optoelectronic devices. Here, a synthetic strategy is presented to prepare nanostructures of a CPP suitable to be used as photoelectrode in a photoelectrochemical (PEC) cell. In this way, electronic and photoelectrochemical properties are measured and, attending to the optoelectronic properties, two hybrid photoelectrodes (photoanode and photocathode) are designed and built to assemble a tandem PEC cell. The final device exhibits photocurrents of 0.5 mA cm −2 at a 0.7 V in the two electrode configuration and the hydrogen evolution reaction is observed and quantified by gas chromatography, achieving 581 µmol of H2 in a one‐hour reaction. Abstract : The use of organic conjugated porous polymers in photoelectrochemical cells is limited by the large particles that typically result from their synthesis. In this work, a synthetic strategy for the nanostructuring of a conjugated porous polymer (IEP‐1) and its successful application as a photoelectrode in both a single system and a tandem PEC is presented, resulting in the hydrogen evolution reaction.